Toad poisoning in Laos. - Keomany, S; Mayxay, M; Souvannasing, P; Vilayhong, C; Stuart, B; Srour, L; Newton, P (2007)
We describe two patients who developed severe illness after eating the skin and eggs of a toad, probably Bufo melanostictus Schneider, in southeastern Laos. One boy died, and one developed a digoxin toxicity-like syndrome with bradycardia and heart failure but survived. A telephone survey of 16 Lao provincial hospitals suggested that toad poisoning occurs in at least six provinces. That 93% of villagers in three villages in southeastern Laos were aware that toads are poisonous but that 51% had encountered patients with toad toxicity suggests that the potential gravity is not appreciated. These data indicate that toad poisoning may be underestimated and that education on the seriousness of toad toxins could be a useful public health measure.